The October Crisis, 1970 : an insider's view - Tetley, William, 1927- (McGill-Queen's University Press, 2007)
"Using now available documentation and his 1970 diary, William Tetley addresses important questions about the October Crisis. In a detailed analysis of the government's decision-making process, Tetley points out what most historical interpretations ignore: all but sixty of those apprehended were soon released, not a window was broken, and the calm that descended on Quebec and Canada has lasted for thirty-six years."--Résumé de l'éditeur.